Rapid keck spectroscopy of cataclysmic variables - Skidmore, W; Horne, K; Pearson, K; Gomer, R; O'Brien, K; Oke, B (2004)
We present an analysis of Rapid Keck Spectroscopy of the CVs AM Her (polar) and SS Cyg (dwarf nova). We decompose the spectra into constant and variable components and identify different types of variability in AM Her with different characteristic timescales. The variable fiickering component of the accretion disc flux and the observational characteristics of a small are in SS Cyg are isolated. © Copyright 2004: IA, UNAM.